1988
DOI: 10.1017/s0890060400000536
|View full text |Cite
|
Sign up to set email alerts
|

A model of the mechanical design process based on empirical data

Abstract: This paper describes the task/episode accumulation model (TEA model) of non-routine mechanical design, which was developed after detailed analysis of the audio and video protocols of five mechanical designers. The model is able to explain the behavior of designers at a much finer level of detail than previous models. The key features of the model are (a) the design is constructed by incrementally refining and patching an initial conceptual design, (b) design alternatives are not considered outside the boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
155
0
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(170 citation statements)
references
References 16 publications
8
155
0
7
Order By: Relevance
“…The models convey insights that might be useful for teaching design, as well for developing AI approaches to either assist or automate design reasoning (Ullman et al 1988). They might not all directly support working designers, but models discussed in this subsection have explanatory power and some have inspired the development of procedural and analytical work.…”
Section: Micro-level Abstract Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The models convey insights that might be useful for teaching design, as well for developing AI approaches to either assist or automate design reasoning (Ullman et al 1988). They might not all directly support working designers, but models discussed in this subsection have explanatory power and some have inspired the development of procedural and analytical work.…”
Section: Micro-level Abstract Modelsmentioning
confidence: 99%
“…For instance, Ullman et al (1988) develop the Task-Episode-Accumulation (TEA) model to explain nonroutine mechanical design by analysing protocol recordings of designers working on such problems. Their model describes design as a series of tasks, each comprised from episodes that are undertaken to achieve goals.…”
Section: Models That Represent Design As Elementary Operationsmentioning
confidence: 99%
“…In comparing the differences between representations favoured by the 2 disciplines, Veveris (1994) observed that engineering designers used models associated with engineering principles, functional mechanisms, production issues; whereas industrial designers applied representations related to appearance and usability. Despite the various attempts to classify representations by other authors (Tjalve et al 1979;Ullman, 1988;Tovey, 1989;Evans, 1992;Ferguson, 1992;Goldschmidt, 1992;Veveris, 1994;Kavakli et al, 1998; 7 Cross, 1999;Do et al, 2000;Otto and Wood, 2001;Cain, 2005 Although ambiguous representations possess benefits, their ill-defined nature makes it difficult for engineering designers to comprehend and recognise how they work in relation to a product's technical parameters (Saddler, 2001). It may be difficult for a viewer other than the originator to understand the embodied meaning, context or scale (McGown, et al, 1998).…”
Section: Standardising the Use Of Design Representationsmentioning
confidence: 99%
“…In comparing the differences between representations favoured by the 2 disciplines, Veveris (1994) observed that engineering designers used models associated with engineering principles, functional mechanisms, production issues; whereas industrial designers applied representations related to appearance and usability. Despite the various attempts to classify representations by other authors (Tjalve et al 1979;Ullman, 1988;Tovey, 1989;Evans, 1992;Ferguson, 1992;Goldschmidt, 1992;Veveris, 1994;Kavakli et al, 1998;Cross, 1999;Do et al, 2000;Otto and Wood, 2001;Cain, 2005 (Rodriguez 1992, Ehrlenspiel and Dylla 1993, Fish 1996. They enable seeing things in a different way that in turn produces new designs and allows flexibility in terms of design attributes.…”
Section: Standardising the Use Of Design Representationsmentioning
confidence: 99%
“…In reverse design, the inputs comprise the set of such descriptors attendant to each of the given components and subassemblies of an existing design. Since there is little evidence of design proceeding exclusively in the forward mode, descriptors from related but independent designs will always be present (Ullman et al, 1988). In this section we describe a representation of and a systematic approach…”
Section: Inputsmentioning
confidence: 99%